2014
DOI: 10.1667/rr13547.1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Airway Remodeling Proteins in Mast Cell Activated by TGF-β Released in OVA-Induced Allergic Responses and Their Inhibition by Low-Dose Irradiation or 8-oxo-dG

Abstract: Allergic asthma is characterized by chronic airway remodeling, which is associated with the expression of extracellular matrix proteins (ECM) by TGF-β. However, to date there are no reports demonstrating that structural proteins are directly expressed in mast cells. This study aimed to investigate whether ECM proteins are expressed in mast cells activated with antigen/antibody reaction, and whether the resolution effects of irradiation or 8-oxo-dG may contribute to allergic asthma prevention. Bone marrow-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(67 reference statements)
0
8
1
1
Order By: Relevance
“…These results indicate that low-dose irradiation does not aggravate asthmatic responses, but attenuates these effects. A previous study has demonstrated that fractionated irradiation at 5 Gy aggravated the severity of asthma [ 10 ], while it was attenuated by 2 Gy irradiation [ 13 , 14 ]. The difference between these previous reports and the present findings could be due to the differences in the dosage and dose rate of irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that low-dose irradiation does not aggravate asthmatic responses, but attenuates these effects. A previous study has demonstrated that fractionated irradiation at 5 Gy aggravated the severity of asthma [ 10 ], while it was attenuated by 2 Gy irradiation [ 13 , 14 ]. The difference between these previous reports and the present findings could be due to the differences in the dosage and dose rate of irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated the relationship between radiation exposure and the development of asthma [ 10 12 ], but the results have been contradictory. While one study reported that radiation exposure induced chronic airway inflammation, another study demonstrated that the asthmatic response was attenuated by radiation [ 13 , 14 ]. These conflicting results have been attributed to the radiation dose and rate used.…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies opposed it through showing LDR (0.1 and 0.2 Gy) reportedly promoted cell death, inflammation, ROS generation (lipid oxidation), and DNA damage (5-hydroxymethylcytosine); and activated damage responses (p53, p38, p21, ERK1/2, NF-κB, TGF-β, etc.) in the lung, these studies unanimously agreed that certain irradiation conditions resulted in less severe changes in lung than that in the liver and the spleen ( Sypin et al, 2003 ; Avti et al, 2005 ; Lee et al, 2006 ; Kim et al, 2007 , 2015 ; Hong et al, 2014 ; Jangiam et al, 2018 ). Moreover, the protective roles of LDR in the lung have been demonstrated in various stress models.…”
Section: The Organ-specific Effects Of Ldr In Cell and Mouse Modelsmentioning
confidence: 81%
“…TGFb is one of a family of multifunctional peptides that regulate proliferation, differentiation, migration, and other functions in tumor immunology. In prostate OVA-expressing transgenic mice, TGFb-mediated repression of T cell function contributed to tumor immunity escapes [45]. Jayaraman et al [46] showed that inhibition of TGFb production boosted tumor-infiltrating CD8 ?…”
Section: Discussionmentioning
confidence: 99%